DIGITAL HUMANIZATION OF EDUCATION IN THE LIGHT OF GEOPOLITICAL CHALLENGES - Mietule, Iveta; Purii, Hanna; Maksymova, Irina; Shaikan, Andrii; Hushko, Serhii; Kulishov, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article examines systemic conditions and important determinants of the humanization of higher education in the light of crucial geopolitical challenges. Complex analysis of the international background of educational humanization is provided on the basis of world rankings given by international network of universities for European countries. The research discloses the most highlighting tendencies towards modern knowledge and education system in the conditions of innovation progress, digital transformation and sustainable development. The analysis reveals logical coherence between humanization, national education, and economic growth. The role of humanization of education is also considered, taking into account the requests of the world labor market, that shapes the most demanded personal criteria in different occupation areas. The concept of human-centrism of the educational system and its components are presented towards economic, geopolitical, digital and environmental discourse. It is concluded that higher education in EU and Ukraine quickly responds to crisis situations and becomes a necessary foundation for comprehensively overcoming the relevant challenges. The research represents authors’ vision on the issue of digital humanization of education and reveals its empiric model.